UNEARTHING ACCOUNTABILITY AND ALLIGNMENT OF SUSTAINABILITY REPORT TO SUSTAINABLE DEVELOPMENT GOALS - Sulistiyowati, Firma; Dewi, Novita; Isti'anah, Arina (Sanata Dharma University, 2025)
Sustainability reports provide a corporate performance’s comprehensive view from economic, social, and environmental perspectives to help stakeholders identify progress and areas for improvement as well as increasing public awareness. However, given the rising issue of “greenwashing,” false environmental claims often shown in company reports, it is important to examine the authenticity of a sustainable report, especially in its alignment with the Sustainable Development Goals (SDGs), to see whether the report actually reflects ecological responsibility or simply to improve stakeholder trust and company image. This study aims to examine the sustainability report of a fishery industry in Indonesia. Using a mix-method, i.e., combination of AI tools for initial summary of the report and qualitative Ecological Discourse Analysis (EDA), especially the framing and erasure theories of Stibbe (2015), the research seeks to identify the report’s alignments with indicators concerning responsible consumption (SDG 12), climate action (SDG 13), and ocean ecosystems (SDG 14). The finding shows that there are inconsistencies between the company’s ecological principles and its sustainability claims as revealed from its framing and erasure narrativization. The report’s focus on creating a corporate self-image as a consumer and market-driven company results in a lack of visible ecological accountability.